Codonopsis radix: a review of resource utilisation, postharvest processing, quality assessment, and its polysaccharide composition - Liang, Wei; Sun, Jiachen; Bai, Gang; Qiu, Daiyu; Li, Qian; Dong, Pengbin; Chen, Yuan; Guo, Fengxia (Frontiers in Pharmacology, 2024)
Codonopsis radix is the dried root of C. pilosula (Franch.) Nannf., C. pilosula Nannf. var. modesta (Nannf.) L. T. Shen, or C. tangshen Oliv., constitutes a botanical medicine with a profound historical lineage. It encompasses an array of bioactive constituents, including polyacetylenes, phenylpropanoids, alkaloids, triterpenoids, and polysaccharides, conferring upon it substantial medicinal and edible values. Consequently, it has garnered widespread attention from numerous scholars. In recent years, driven by advancements in modern traditional Chinese medicine, considerable strides have been taken in exploring resources utilization, traditional processing, quality evaluation and polysaccharide research of Codonopsis radix. However, there is a lack of systematic and comprehensive reporting on these research results. This paper provides a summary of recent advances in Codonopsis research, identifies existing issues in Codonopsis studies, and offers insights into future research directions. The aim is to provide insights and literature support for forthcoming investigations into Codonopsis.